1982
DOI: 10.1128/iai.38.3.1109-1116.1982
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a gene in Vibrio cholerae that determines the antigenic structure of cholera toxin

Abstract: In Ouchterlony-type immunodiffusion gels, the cholera toxin produced by the classical Vibrio cholerae strain 569B was indistinguishable from the cholera toxin of the Eltor strain RJ1. However, the cholera toxin produced by both of these strains was incompletely cross-reactive with the cholera toxin produced by the Eltor strain 3083-2. The allele of the gene responsible for the 569B and RJ1 type of toxin was designated vct-1, and the allele responsible for the 3083-2 type of toxin was designated vct-2. The vct-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Toxin regulatory differences between various strains and mutants of V. cholerae have previously complicated the genetic analysis of the toxin structural genes (2,19,20,29,30). For example, Saunders et al (29) reported the mapping of a V. cholerae gene, vct, which is responsible for an antigenic variation in the cholera toxin produced by the two El Tor strains 3083 and RJ1 (the latter is the same as strain RV79).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toxin regulatory differences between various strains and mutants of V. cholerae have previously complicated the genetic analysis of the toxin structural genes (2,19,20,29,30). For example, Saunders et al (29) reported the mapping of a V. cholerae gene, vct, which is responsible for an antigenic variation in the cholera toxin produced by the two El Tor strains 3083 and RJ1 (the latter is the same as strain RV79).…”
Section: Discussionmentioning
confidence: 99%
“…Since our data place the toxin structural genes between these two loci, it is possible that Saunders et al did not recognize certain important vet or ctx recombinant classes in their analysis. The conflicting data might also be due to the fact that Saunders et al (29,30) used, in these genetic analyses, heterologous crosses between two different El Tor strains, RJ1 and 3083.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transposon-facilitated recombination system of Johnson and Romig (4) was used in conjunction with an RJ1 donor strain and a 3083-2 recipient strain to map the position of tox-1000. The procedural details of the mating experiments have been previously described (6). Strain MB2020(pSJ13) (RJ1: :Tnl-24, vct-i, tox-1000, and rif-5001) was used as the donor strain.…”
mentioning
confidence: 99%
“…In conjugal matings, Tfr donors transfer the bacterial chromosome to recipient bacteria in an oriented and sequential manner from an origin corresponding to the site of insertion of the transposon in the donor chromosome. Isogenic Tfr donor strains with P plasmids containing the appropriate transposon in opposite orientations can, therefore, mobilize chromosomal genes in conjugal matings from a common origin but with opposite polarities (10,16,17). In the studies reported here, we used transposon-facilitated recombination mediated by transposon Tnl or transposon TnS for genetic mapping of biotype determinants of V. cholerae.…”
mentioning
confidence: 99%